Avaliação dos efeitos da viscosidade do fluido e da concentração e granulometria da areia na contenção de areia em telas stand alone - Pinheiro, Rafael de Paula (2021)
Sand production affects more than 70% of oil and gas reservoirs worldwide and, to control the impacts of solids production in a well, some mechanisms have been developed over the years, including the Stand Alone Screen system. Despite the range of published works on the subject, studies that aim to verify the influence of the characteristics of the transport fluid and the solids carried on the cake formation and, consequently, on the pressure drop observed for screens of containment are still scarce in the literature. For this reason, this work proposes to develop a bench and experimentally evaluate the effects of fluid viscosity and sand granulometry and concentration of cake formation, pressure drop, flow rate and permeability of the system. The experimental apparatus developed allows the transport of a fluid containing sand through a set of premium screens composed of a wire wrapped screen and a metallic mesh screen. The tested sand mass are between 0.05% and 0.15%, fluid viscosities between 9 and 47 cP and sands with characteristic sizes of 268 μm and 692 μm. The results obtained in the tests show that the sand retention can be divided into two regions. In the first, depth filtration occurs, the pressure drop increases significantly, with increments between 30 and 120 kPa. In the second region, surface filtration occurs, the pressure drop assumes a more linear behavior and grows less sharply, with increments between 10 and 30 kPa. Increasing the pressure drop results in reduced flow. The measured viscous permeability ranges from 5.40x10-4 m² to 3.66x10-5 m² and the inertial permeability values range from 5.29x10-2 m to 6.55x10-1 m. The tests performed show results that have physical consistency, coherence and qualitative agreement with the results found in the literature. The results show that the greater the height of the formed bed, the greater the observed pressure drop, however, flows with transport fluid with lower viscosity, less concentrated solutions and flows with smaller particle size, give rise to a lesser sand bed. permeable. The measurement of pressure drop, flow rate, bed height and the calculation of the system's permeability provide the basis for studying the physical phenomena that occur during sand retention and the filtration process. The as-built bench allows the execution of future works under different conditions, being versatile for the experimentation and selection of sand containment screens.